ANALISIS KOMPETENSI EKSPLORASI MATEMATIS SISWA KELAS X PADA MATERI FUNGSI KOMPOSISI - Indah Wahyuni; Endah Alfiana (INSPIRAMATIKA, 2022)
Mathematical exploration competence is formed from the encouragement of students in digging up information including concepts, creative thinking, critical thinking, reasoning, being able to solve problems experienced, which are then revealed the results of the knowledge found previously. The purpose of this study was to analyze and determine the mathematical exploration ability of class X students in the composition function material. The research method that the researchers took was a type of qualitative research in the form of descriptive research. The research subjects selected were students from class X Religion at MAN 1 Probolinggo City. The results showed that the students' mathematical exploration abilities in high-level categories were able to meet the six indicators, namely being able to interpret or understand a mathematical problem, examine patterns that had been found, carry out searches in an informal way, clarify or examine efforts in problem solving, and symbolize and generalization. While at a low level of ability, they are able to meet all four indicators, but cannot fulfill the stage of interpreting or understanding the problem and making generalizations. Students who have a low level of ability are only able to fulfill both indicators, but are unable to complete interpreting or understanding problems, clarifying efforts in solving problems, symbolizing and generalizing.